Psychological and Organizational Contexts for Handball Coaches from the Players’ Point of View - Majid Mohammed Msaed1 , Muhammad Shabram Alwan1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Importance of research came through the study of Organizational Fairness for handball coaches from theplayer’s point of view as a modest contribution to the advancement of the handball game. The importanceof achieving Organizational Fairness in the distribution of duties and rights to the players equally by thecoach in the sports team as one of the small groups and this characteristic has a direct impact on the levelof players technically, skilled, physically and psychologically, and this indicates the cases of dedication andthe high effort to achieve the goals. As for the recommendations, it is the adoption of the current scale bythose interested to periodically uncover the level of Organizational Fairness for coaches clubs by hand intraining and competition and to benefit from the current scale as an objective research tool by researchersand use it in their research and studies, and it is necessary to inform the trainers of the importance ofOrganizational Fairness in the sports field when It has an impact on the level of team achievement and theplayers ’performance in particular in training and competition in order to work on developing it for theplayers.